Flexible supercapacitor electrodes based on real metal-like cellulose papers - Yongmin Ko (Nature Portfolio, 2017)
With ligand-mediated layer-by-layer assembly between metal nanoparticles and small organic molecules, the authors prepare metallic paper electrodes for supercapacitors with high power and energy densities. This approach could be extended to various electrodes for portable/wearable electronics.